Automotive engine performance / James D. Halderman - Halderman, James D. 1943- (Pearson/Prentice Hall, 2007)
Written in and for the 21st century, this comprehensive book is divided into chapters that correspond to the content area of certification as specified by the National Institute for Automotive Service Excellence (ASE) and the National Automotive Technicians Education Foundation (NATEF).